Deep simplicity. The dangers of intervention in curriculum - Kushner, Saville (Revista IRICE, 2012)
The article analyses the position of two important educational thinkers: A.S. Neill and L. Stenhouse. The author finds the radicalism of their position in their confidence to stand back, to see curriculum not as an intervention, but as a set of conditions for learning. Both theorists shared an educational principle: that complexity of intervention interrupted and did not guarantee the quality and the freedom of learning. They saw educational quality in terms of complexity –yes– but complexity situated elsewhere than in interventions. From these perspectives, the author questions the present educational situation, where he finds that the power of the “single narrative” to determine interactions is a general principle of social and political life.